EMPATHY-TO-EXECUTION (E2E): AN EXECUTION-ORIENTED DESIGN THINKING MODEL FOR META-SKILLS–BASED ACADEMIC SYSTEM TRANSFORMATION - Che, Chi; Chaemchoy, Sukanya; Siribanpitak, Pruet (Journal of Education and Innovation, 2026)
Academic systems often generate reform ideas but struggle to sustain execution at scale. This brief synthesis draws on multiphase-mixed-methods-research in private higher education institutions in Sichuan Province, China, combining a student meta-skills survey (n = 400) and an institutional stakeholder needs assessment (n = 805) with PNImodified to rank gaps, alongside design-thinking-guided development and expert validation of an innovation framework. Student meta-skills were moderate-to-high overall, yet item-level patterns revealed weaker performance in uncertainty handling and continuous strategic recalibration; institutional diagnostics identified curriculum structuring and learning engagement as the highest priority needs (followed by instructional design), indicating that structural and experiential learning conditions are key constraints on meta-skills development. Building on these findings, this study proposes an Empathy-to-Execution (E2E) model that preserves design thinking while adding execution requirements—decision-grade prioritization, implementation artifacts, and scaling governance—implemented through three validated modules (Agile Meta-skills Integration, Immersive Experiential Pedagogy, Smart Meta-skills Assessment) to align curriculum, pedagogy, and evaluation for sustainable institutional transformation. Theoretically, E2E extends Design Thinking by specifying an institutional execution layer—decision-grade prioritization, artifact-based implementation, and governance-for-scaling—that translates prototypes into durable academic routines.